Bacteriological survey and detection of Escherichia coli, Salmonella spp., streptococcus spp., and vibro spp. in bottom sediments from two sites in Iloilo River. - Barrera, Christopher
Bacterial contamination in the Iloilo river occurs because of various human activities. The assessment of the river was done using microbiological parameters (HPC, TC, FC, and FS)for 7 months in Sooc Bridge and Carpenter's Bridge using bottom sediments for sampels. Sediment was used because bacteria accumulate over time in the sediment due to high amounts of organic and inorganic matter in the substrate and this leads to better survivability of bacteria. The values obtained from microbiological parameters investigated are generally higher in Sooc Bridge. HPC results show that the higher mean value was in Sooc Bridge (7.43 x 10 raised to 8th power CFU/100g). The levels of TC on both sampling sites ranged from 9.5 x 10 raised to the 2nd power to 2.40 x 10 raised to the 4th power CFU/100g. For TC' Sooc has the higer mean (1.76 x 10 raised to the 4th power CFU/100g) for 7 months. FC values ranged from 3.0 x 10 raised to 1st power to 2.4 x 10 raised to the 4th power CFU/100 g. Sooc bridge has the higher mean (1.17 x 10 raised to the 4th power CFU/100g) between the 2 sites. Lastly, the FS value range from 2.9 x 10 raised to the 3rd power to 2.4 x 10 raised to the 4th power CFU/100g. Also, Sooc Bridge has the higher mean value (1.58 x 10 raised to the 4th power CFU/100g). There are nosignificant differences on the microbiological parameters used in each site. The FC/FS ratio revealed that mixed fecal materials contaminate the river. Among the four pathogenic bacteria detected, Salmonella spp. was the most abundant for 7 months (63-65 percent) and E. coli was the least abundant (>1 percent). Based on the criteria on sediment quality evaluation, there is little to moderate loading of organic and inorganic matter.